(2+3i)+(c+di)=2+i

Simple and best practice solution for (2+3i)+(c+di)=2+i equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2+3i)+(c+di)=2+i equation:


Simplifying
(2 + 3i) + (c + di) = 2 + i

Remove parenthesis around (2 + 3i)
2 + 3i + (c + di) = 2 + i

Remove parenthesis around (c + di)
2 + 3i + c + di = 2 + i

Reorder the terms:
2 + c + di + 3i = 2 + i

Add '-2' to each side of the equation.
2 + c + di + -2 + 3i = 2 + -2 + i

Reorder the terms:
2 + -2 + c + di + 3i = 2 + -2 + i

Combine like terms: 2 + -2 = 0
0 + c + di + 3i = 2 + -2 + i
c + di + 3i = 2 + -2 + i

Combine like terms: 2 + -2 = 0
c + di + 3i = 0 + i
c + di + 3i = i

Solving
c + di + 3i = i

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1di' to each side of the equation.
c + di + -1di + 3i = -1di + i

Combine like terms: di + -1di = 0
c + 0 + 3i = -1di + i
c + 3i = -1di + i

Add '-3i' to each side of the equation.
c + 3i + -3i = -1di + i + -3i

Combine like terms: 3i + -3i = 0
c + 0 = -1di + i + -3i
c = -1di + i + -3i

Combine like terms: i + -3i = -2i
c = -1di + -2i

Simplifying
c = -1di + -2i

See similar equations:

| 14d^2=-27d | | (-12x+4x)+(6-12)= | | 5x-2x+x=9+3x+10 | | 9(8+8g)= | | 20-2(1/2) | | 3(9x+2)+8-16x= | | .5x+.1x=8 | | 6/12÷6/6 | | 5a^2-4ab+16b=0 | | 2.3=43.7 | | 4(6-2y)=64 | | 5a^2-4ab-16b=0 | | -6=x/9-7 | | 5/4x=9/4 | | 30+(4x+20)+(x+5)=180 | | 7(-9t+-9)+t= | | 3x-6-4x+9= | | 2+6n=18 | | 6n-12=96 | | 34c-13=55 | | 34c-13=15 | | 9tanx+2=7 | | W=3a-5n | | (2x-8)(x)=330 | | 20/(4-(10)) | | -22+2x=-8 | | 6r+29=83 | | 3x-6y=-3(30) | | C=F-32/1.8 | | Y=in(x+3) | | 8(4x+5y)=(5y*8)+4 | | 6+2x=5+7x |

Equations solver categories